2019
DOI: 10.1007/s12028-019-00733-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intracranial Pressure Attenuates the Pulsating Component of Cerebral Venous Outflow

Abstract: BackgroundThe underlying physiology of the intracranial pressure (ICP) curve morphology is still poorly understood. If this physiology is explained it could be possible to extract clinically relevant information from the ICP curve. The venous outflow from the cranial cavity is pulsatile, and in theory the pulsatile component of venous outflow from the cranial cavity should be attenuated with increasing ICP. In this study, we explored the relationship between ICP and the pulsatility of the venous outflow from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…While this effect is most easily observed in sheep F, it can also be observed in all sheep where ITP to ICP communication existed. Minimal CVP reaction was observed across the infusion study both in mean and pulse, corresponding to previous literature stating that elevated ICP serves to attenuate venous pulse reactions [ 29 ].…”
Section: Discussionsupporting
confidence: 76%
“…While this effect is most easily observed in sheep F, it can also be observed in all sheep where ITP to ICP communication existed. Minimal CVP reaction was observed across the infusion study both in mean and pulse, corresponding to previous literature stating that elevated ICP serves to attenuate venous pulse reactions [ 29 ].…”
Section: Discussionsupporting
confidence: 76%
“…Their results are consistent with the present study. A recent study also reported that increased ICP attenuates the pulsatility of cerebral venous out ow [26] .…”
Section: Interpretation Of the Decreased Pimentioning
confidence: 85%
“… 61 Not only do these large movement cause significant increase of ICP, small movements, such as twitching and changes in body position, 111 can increase ICP dramatically. It is important to understand the ICP change and its relation with different behaviors, because ICP elevation alters CSF clearance pathways, 163 , 164 affects venous outflow dynamics 165 and determines sympathetic activity. 166 , 167 Increases in ICP are also associated with pathology.…”
Section: Other Physiological Signal Monitoringmentioning
confidence: 99%